PENGARUH PRAKTIK SUMBER DAYA MANUSIA STRATEGIK DAN KNOWLEDGE MANAGEMENT TERHADAP KINERJA ORGANISASI - Basuki Basuki (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2015)
The purpose of this paper is to discuss the relationship between the variables of the practice of strategic human resource management and quality of service. The approach of this discussion is to do a literature study and review the results of previous studies Results of the discussion showed that the practice of strategic human resource management has a relationship to the quality of service but can not be proven empirically. Limitations of this study that this research study area only on the territory of South Kalimantan, would narrow the generalizability of research findings to other areas or regions wider coverage. The data presented in this study is a cross sectional shape that only represent certain point of time only. In this study, the measurement variables of service quality and organizational performance is measured from the perspective of internal organization, future studies should also involve external respondent organizations.